Uso de nuevas tecnologías y logros de aprendizaje en niños de cuatro años de la Institución Educativa Inicial N° 756 del distrito de Iquitos 2023 - Bocanegra Chuquizuta, Belen (2025)
The research aimed to examine the relationship between the use of new technologies and learning achievements in four-year-old children from the Initial Educational Institution No. 756 in the district of Iquitos during 2023. To achieve this, 70 parents and two teachers participated, responding to carefully designed questionnaires to gather accurate information. The study was relational in nature, and to test the hypothesis, the non-parametric Spearman statistical test was applied, which clearly measured the link between both variables. The results were conclusive: a very high positive correlation was found (Spearman: 0.928; significance 0.000), suggesting that the use of new technologies is closely linked to better learning achievements in children.